2001
DOI: 10.1074/jbc.m108522200
|View full text |Cite
|
Sign up to set email alerts
|

Second Transmembrane Domains of ENaC Subunits Contribute to Ion Permeation and Selectivity

Abstract: Epithelial sodium channels (ENaC) are composed of three structurally related subunits (␣, ␤, and ␥). Each subunit has two transmembrane domains termed M1 and M2, and residues conferring cation selectivity have been shown to reside in a pore region immediately preceding the M2 domains of the three subunits. Negatively charged residues are interspersed within the M2 domains, and substitution of individual acidic residues within human ␣-ENaC with arginine essentially eliminated channel activity in oocytes, sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 45 publications
5
35
0
Order By: Relevance
“…Amiloridesensitive sodium currents measured in oocytes by two-electrode voltage clamp the following day indicated that all combinations of epitope-tagged subunits produce functional sodium channels with amiloride-sensitive whole cell currents in the range of 7-27 A/oocyte, similar to whole cell currents we have observed with wild type ENaC (27,29). Because these data indicate that the epitope-tagged ␣␤␥ENaC subunits produced functional amiloride-sensitive sodium channels, they were used to study ENaC assembly and processing.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…Amiloridesensitive sodium currents measured in oocytes by two-electrode voltage clamp the following day indicated that all combinations of epitope-tagged subunits produce functional sodium channels with amiloride-sensitive whole cell currents in the range of 7-27 A/oocyte, similar to whole cell currents we have observed with wild type ENaC (27,29). Because these data indicate that the epitope-tagged ␣␤␥ENaC subunits produced functional amiloride-sensitive sodium channels, they were used to study ENaC assembly and processing.…”
Section: Resultssupporting
confidence: 67%
“…The mENaC subunit cRNAs (1 ng per subunit) were injected into oocytes, and electrophysiological measurements were performed after 24 h as described previously (27). The difference in measured current in the presence and absence of amiloride (100 M) was used to identify ENaC currents produced by different subunit combinations.…”
Section: Methodsmentioning
confidence: 99%
“…The residues that form the putative amiloride-binding site (␣Ser 583 , ␤Gly 525 , and ␥Gly 542 ) are at the site where the pore ␣-helix transitions to an extended selectivity filter (17). Our earlier work indicated that the second membrane-spanning domains of ENaC have a secondary selectivity site, and we suggested that M2 may have an "inverted teepee" structure similar to that of KcsA (18). The apparent lack of accessibility of ␣␤G525C␥ to MTSET is consistent with a pore region structure similar to that of the KcsA K ϩ channel.…”
supporting
confidence: 66%
“…To our knowledge, no Na + -specific nucleic acid, whether naturally occurring or in vitro selected has been previously reported. In the protein world, although K + channels are quite selective for K + over other metal ions, the Na + channels are much less selective (75,76). Being able to obtain the NaA43 DNAzyme with such a high selectivity for Na + will not only provide a highly selective sensor for Na + , as demonstrated here, it will also give us an opportunity to elucidate the origin of such a high selectivity.…”
Section: Discussionmentioning
confidence: 78%